Tradisi Upacara Kematian Umat Khonghucu dalam Perspektif Psikologis - Marmiati Mawardi (Analisa: Journal of Social Science and Religion, 2010)
Based on the Con fu tse ’s teaching, life is a long journey without an end.Birth is an entrance to the world. Death is an exit door from the world. Life inhereafter is a continuation of life in the world. Therefore, all of the human’sdeed in the world will affect their life in hereafter. This article about deathceremony of Confucian is part of finding of my research on the religious lifedevelopment to the Chinese who believes in Confucion in Surakarta. Deathceremony has psychological values which influence one’s attitude and characterin his/her life in the world. Keywords : Death Ceremony, Confucion, Psycology